Bio-Mediated Soil : A Sustainable Ground Improvement Technique - Min Le, Lee (Himpunan Ahli Teknik Tanah Indonesia (HATTI), 2014)
ABSTRACT: Bio-mediated soil has recently emerged as a new and sustainable soil improvement technique. This paper presents the results of investigation on the performances of bio-mediated soil improvement on sand and a typical tropical residual soil (sandy silt). A species of Bacillus group, B. megaterium was used to trigger calcite precipitation. The treatments were performed at various soil densities (85%, 90% and 95% maximum density), and treatment conditions (untreated, treated with cementation reagents only, and treated with B. megaterium and cementation reagents). Results showed that the MICP treatment which was often attempted on sand was equally robust in tropically residual soil. The shear strength of MICP-treated residual soil was improved by 40 - 164% compared to its untreated counterpart. The saturated hydraulic conductivity of the MICP-treated residual soil was reduced by 54 - 74%. The effectiveness of the bio cementation and bio clogging in residual soil was mainly governed by the particle-particle contacts, porosity and pore spaces between soil particles. Future research may focus on in-situ applications of bio-mediated soil improvement and its effectiveness in fine-grained soils. Keywords: bio-mediated soil improvement, microbially induced calcite precipitation, biocementation, bioclogging, residual soil